Economic reactions to public finance consolidation - a survey of the literature - Maria Gabriella Briotti (European Central Bank (ECB), 2005)
The paper reviews the theoretical and empirical literature that has investigated the conditions under which a contractionary fiscal policy is effective in reducing debt and deficit, but does not have a negative effect on growth. The issue is central to macroeconomics and policy making, given that many countries are currently facing increasing fiscal imbalances, with additional pressure coming in the medium term from population ageing. The paper concludes that the theoretical impact of fiscal policy on aggregate demand and economic activity depends largely on the conceptual framework considered and its assumptions about the world. Empirical studies based on macro-econometric model simulations find evidence that fiscal consolidations lead initially to production losses, while they can result in a higher output in the medium term. Empirical studies focusing on episodes of changes in fiscal policies provide in turn evidence that under certain circumstances austerity measures may have an expansionary impact on the economy.
Keywords: E62; H30; 330; fiscal multiplier; fiscal consolidation; non-Keynesian effects; government spending and taxing.; Haushaltskonsolidierung; Wirtschaftswachstum